THE EFFORT OF IMPROVING THE PERFORMANCE OF TEACHERS WHO GOT AN ADDITIONAL ASSIGNMENT AS A HOMEROOM TEACHER AT MIN 1 WEST ACEH IN ACADEMIC YEAR 2020-2021 - Lidan, M (Program Studi Pendidikan Bahasa Indonesia FKIP-UNIVA Medan, 2021)
The problem that was served as the basis of this study was the lack of teachers’ professionalism in teaching which was brought on by: (1) The homeroom teacher who got an additional assignment as a teacher was one of the factors which determined the success or failure of the learning process. With all the duties as a homeroom teacher, he or she sometimes forgot his or her main duties as an educator (2) The suitability between educational qualifications and the subjects taught was still a separate problem. Though educational qualifications will affect productivity, work discipline and work performance. Homeroom teachers who got an additional assignment as a teacher whose educational background was different from the subject they taught would tend to be undisciplined in teaching, and only fulfill administrative requirements regarding the provision of teaching hours. An effort was made to fix the weaknesses as described above by carrying out a school action research activity. The principal’s effort in Improving the Performance of Teachers Who Got Additional Assignment as a Homeroom Teacher was by having the Teachers’ Performance Assessment at MIN 1 West Aceh. While the aim was to find out the description of the performance of the homeroom teachers’ who were given an additional assignment as a teacher at Min 1 West Aceh for the 2021-2022 academic year. Data collection techniques used were observation and documentation activities. The data analysis technique used was a flow model recorded in field notes, which consisted of three flow activities that took place simultaneously, namely data reduction, data presentation, and drawing conclusions. The results showed that the implementation of teachers’ performance appraisal as an effort to improve the performance of teachers who got an additional assignment as a homeroom teacher at MIN 1 West Aceh was scientifically proven. It can be seen from the results in each cycle. The performance of teachers who got an additional assignment as a homeroom teacher after the performance assessment was carried out was only one teacher or 17%, in the first cycle and in the last cycle it increased to 100% or all teachers who got an additional assignment as a homeroom teacher stated that their performance is getting better.